Isolasi Senyawa Manitol dan Ergosterol dari Fraksi Isopropanol Jamur Tanduk (Termitomyces eurrhizus Berk) - BAMBANG MURSITO; PATRICK PATRICK; AHMAD DARMAWAN; LEONARDUS SUGENG BROTO KARDONO (Fakultas Farmasi Universitas Pancasila, 2009)
Jamur tanduk (local name), Termitomyces eurrhizus Berk, is one of mushroome species from genus Termitomyces. The edible mushroom can be found in various areas in Indonesia. In this study, determination of chemical structure of components in the mushroom extract has been made. Based on interpretation of spectra data ultra-violet, infra red, nuclear magnetic resonance one dimension (proton, carbon and DEPT) and NMR two dimension (COSY, HMQC and HMBC), two compounds: mannitol and ergosterol, has been isolated from isopropanol fraction of the extract